(untitled) (Palíndromo, 2022)
Since its birth in the 15th Century, Miniature painting was "intrinsically" the art of playing on details. Coming from the illuminated manuscripts tradition, it became independent from the book industry. Its genesis originated disputes with painters. To avoid fiscal constraints, miniaturists used words and details – their specific use of bodycolor, not oil - at court but without success. Finally enrolled in painters’ guilds, they endeavored to value their works according to various criteria: size and importance of accessories (like the other painters) but also specific ones: the finesse of execution, touches and dots, and the degree of the finishing observable with a magnifier. Attention to details can nowadays contribute to attribution, identification and historical analysis of miniatures and is studied in particular through the van Blarenberghe’s miniatures.